Environmental-social-governance preferences and the holding of crypto-assets - Pavel Ciaian; Andrej Cupak; Pirmin Fessler; D'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2022)
Individuals invest in ESG-assets not only because of higher expected returns but also for ethical and social considerations. Controversies surrounding the ESG footprint of crypto-assets - mainly on grounds of the energy-intensive crypto mining and their use for illegal activities - offer an interesting object of inquiry. Leveraging a unique representative survey for the Austrian population, we examine whether investors' ESG preferences can explain cross-sectional differences in individual portfolio exposure to crypto-assets. While we find no statistically significant relationship between ESG concerns of investors and the probability of holding bonds or shares, in contrast, we find a strong association between investors' ESG preferences and crypto-investment exposure.
Keywords: D14; G11; G41; 330; Crypto-assets; financial behaviour; environmental-social-governance preferences